2017
DOI: 10.35360/njes.413
|View full text |Cite
|
Sign up to set email alerts
|

Genre and change in the Corpus of History English Texts 1

Abstract: This paper provides an overview of the Corpus of History English Texts, one of the component parts of the Coruña Corpus of English Scientific Writing (Moskowich and Crespo 2012), looking in particular at the communicative formats that it contains. Among the defining characteristics of the Coruña Corpus are that it is diachronic in nature, and that it can be considered either as a single-or multi-genre corpus, according to the theoretical tenets adopted (Kytö 2010; McEnery and Hardie 2013). The corpus has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
6
0
4
Order By: Relevance
“…In relation to the textual genres gathered in CC, the samples have been organised in eight groups corresponding to a genre category (see Moskowich, 2017): treatises, essays, textbooks, letters, lectures, articles, dialogues, and others. Moskowich (2011: 182) explains that this classification is not based solely on linguistic features, but also on other aspects, such as epistemological features, social factors and the authors' purposes, for instance.…”
Section: Corpus Description Research Methods and Resultsmentioning
confidence: 99%
“…In relation to the textual genres gathered in CC, the samples have been organised in eight groups corresponding to a genre category (see Moskowich, 2017): treatises, essays, textbooks, letters, lectures, articles, dialogues, and others. Moskowich (2011: 182) explains that this classification is not based solely on linguistic features, but also on other aspects, such as epistemological features, social factors and the authors' purposes, for instance.…”
Section: Corpus Description Research Methods and Resultsmentioning
confidence: 99%
“…New patterns of thought, and new methodological procedures based on observation started to be common practices after the seventeenth century (Taavitsainen 2017: 83), and all this is reflected in technical and scientific texts. As regards the genres represented in CHET, there are samples of articles, essays, lectures, textbooks and treatises written by both male and female authors (Moskowich 2017). CHET includes ca.…”
Section: The Corpus and The Methodsmentioning
confidence: 99%
“…Previous research (Crespo and Moskowich 2016;Moskowich 2017) has shown that both subject matter and communicative format or genre exert a great influence on linguistic choice. The genres included in the CC cover different degrees of formality and proximity to the oral register.…”
Section: Adverbs Modals and Communicative Formatsmentioning
confidence: 99%